The efficacy of ileostomy after laparoscopic rectal cancer surgery: a meta-analysis - Yu Mu; Linxian Zhao; Hongyu He; Huimin Zhao; Jiannan Li (World Journal of Surgical Oncology, 2021)
Abstract Background Protective ileostomy is always applied to avoid clinically significant anastomotic leakage and other postoperative complications for patients receiving laparoscopic rectal cancer surgery. However, whether it is necessary to perform the ileostomy is still controversial. This meta-analysis aims to analyze the efficacy of ileostomy on laparoscopic rectal cancer surgery. Methods Cochrane Library, EMBASE, Web of Science, and PubMed were applied for systematic search of all relevant literature, updated to May 07, 2021. Studies compared patients with and without ileostomy for laparoscopic rectal cancer surgery. We applied Review Manager software to perform this meta-analysis. The quality of the non-randomized controlled trials was assessed using the Newcastle-Ottawa scale (NOS), and the randomized studies were assessed using the Jadad scale. Results We collected a total of 1203 references, and seven studies were included using the research methods. The clinically significant anastomotic leakage rate was significantly lower in ileostomy group (27/567, 4.76%) than that in non-ileostomy group (54/525, 10.29%) (RR = 0.47, 95% CI 0.30–0.73, P for overall effect = 0.0009, P for heterogeneity = 0.18, I 2 = 32%). However, the postoperative hospital stay, reoperation, wound infection, and operation time showed no significant difference between the ileostomy and non-ileostomy groups. Conclusion The results demonstrated that protective ileostomy could decrease the clinically significant anastomotic leakage rate for patients undergoing laparoscopic rectal cancer surgery. However, ileostomy has no effect on postoperative hospital stay, reoperation, wound infection, and operation time. The efficacy of ileostomy after laparoscopic rectal cancer surgery: a meta-analysis.